Synthesis and characterization of poly(L-lactide)-poly(epsilon-caprolactone) multiblock copolymers - Jeon, O; Lee, SH; Kim, SH; Lee, YM; Kim, YH (AMER CHEMICAL SOC, 2003)
New poly((L)-lactide) (PLLA)-poly(c-caprolactone) (PCL) multiblock copolymers were prepared by using the coupling reaction between the bischloroformates of carboxylated PLLA with PCL-diol in the presence of pyridine. All the copolymers were characterized by H-1 NMR and GPC and investigated further by using DSC, TGA, SAXD, WAXD, polarizing microscope, and Instron testing. The molecular weights of PLLA-PCL multiblock copolymers produced lay in the range 40 000-50 000. The multiblock copolymers produced exhibited only one melting peak, corresponding to the PLLA phase, even at a relatively high PCL content, whereas the PLLA-PCL-PLLA triblock copolymers had two melting peaks. The tensile moduli and strengths of the triblock copolymer were very high. On the other hand, the multiblock copolymers were flexible and elastic with relatively good mechanical properties. These copolymers behaved like thermoplastic elastomer due to the presence of physical cross-linking and strain recoveries of more than 95% at 100% strain. Degradation of the copolymers was investigated in PBS for up to 150 days. The random copolymer was found to be rapidly degraded, while the triblock and multiblock polymers were slowly degraded. The molecular weight of the multiblock copolymers decreased with time, but there were no significant changes in their chemical compositions. From 1H NMR studies, chain scission occurred in the PLLA blocks.
Keywords: EPSILON-CAPROLACTONE; DRUG-DELIVERY; L-LACTIDE; POLYMERIZATION